Social Aspect Of The Main Character In Encanto Movie Script - Jazzyca Josephine Tulende; Sudirman Maca; Asyrafunnisa Asyrafunnisa (Humaniora: Journal of Linguistics, Literature, and Education, 2022)
The script made the audience confuse and the actual social influence of the literature. The research aimed is to identify the social aspects that appeared in Encanto movie script and to found out the impacts of the main character to the society in Encanto movie script. The research applied descriptive qualitative method in order to explain the types of social aspects that are found in the Encanto movie script and the impacts of the main character to the society in Encanto movie script with sociological approach. The writer found there are 3 types of social aspects; culture aspects, social environment aspects and economic aspects. The writer also found the impact of the main character to the society which was the main character could influence other character which has an impact of changing people’s perspective on being positive in every way, to not judge book by its cover.